2017
DOI: 10.1186/s12935-017-0489-4
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating CD4+ T cells in patients with gastric cancer

Abstract: BackgroundT lymphocytes play an indispensably important role in clearing virus and tumor antigen. There is little knowledge about impacts of inhibitory molecules with cytokine on tumor-infiltrating CD4+ T-cells in the presence of gastric cancer (GC). This study investigated the distribution of tumor-infiltrating T-cells subset and the differentiation as well as inhibitory phenotype of T-cells from blood and tissues of GC patients.Materials and methodsPatients with GC diagnosed on the basis of pre-operative sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 45 publications
4
29
0
Order By: Relevance
“…M2 macrophages are hypothesized to promote tumor growth, infiltration and metastasis, and their degree of infiltration is negatively correlated with the prognosis of patients (39,40). cd4 + T cells are important for the protection against cancer (41). in the present study, patients in the FGF2-l group had more dendritic cells, cd4 + memory activated T cells, fewer M2 cells, and a higher survival rate.…”
Section: Discussionsupporting
confidence: 49%
“…M2 macrophages are hypothesized to promote tumor growth, infiltration and metastasis, and their degree of infiltration is negatively correlated with the prognosis of patients (39,40). cd4 + T cells are important for the protection against cancer (41). in the present study, patients in the FGF2-l group had more dendritic cells, cd4 + memory activated T cells, fewer M2 cells, and a higher survival rate.…”
Section: Discussionsupporting
confidence: 49%
“…The study of Yuan et al[ 79 ] revealed that gastric cancers present an increased percentage of CD4 + T lymphocytes and lower CD8 + T cells (with an increased CD4 + /CD8 + ratio) compared to blood and, further, to paraneoplastic tissue. In addition, the number of TILs of effector and memory T cell type is significantly higher than in the case of circulating T cells.…”
Section: Host Immune Response In Gastric Cancer Patientsmentioning
confidence: 99%
“…As we have already mentioned, the involvement of Tregs in antitumor immunity is controversial, and their role may differ according to the type of cancer[ 80 , 81 ]. These authors considered CD4 + CD25 high CD127 low as being the most specific marker to define the Treg population, with the percentage of these cells being increased among TILs, demonstrating the accumulation of immunosuppressive Tregs at the site of a gastric tumor[ 79 ]. Recent studies show that the coexpression of PD-1 + and Tim-3 + define the most hypo-functional T lymphocytes[ 32 , 82 ].…”
Section: Host Immune Response In Gastric Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with our result, it has been demonstrated recently that Tregs with suppressive activity were upregulated on tumor-infiltrating T cells from patients with gastric cancer compared with their expressions on corresponding peripheral blood. 28 Furthermore, it has been reported that an increased number of peripheral blood CD8 + T cells can predict a better response to RT in patients with cancer and suggested that antitumor immunity may play Figure 3 Phenotyping and functional characterization of patient's T cells from peripheral blood using flow cytometry. (A) Dot blots represent CD4 + and CD8 + subsets (gated on CD3 + T cells) at disease progression, resolution and re-progression.…”
mentioning
confidence: 99%